Testing the independence of self-reported interoceptive accuracy and attention. Issue 1 (January 2020) - Murphy, Jennifer; Brewer, Rebecca; Plans, David; Khalsa, Sahib S; Catmur, Caroline; Bird, Geoffrey
It has recently been proposed that measures of the perception of the state of one's own body ("interoception") can be categorised as one of several types depending on both how an assessment is obtained (objective measurement vs. self-report) and what is assessed (degree of interoceptive attention vs. accuracy of interoceptive perception). Under this model, a distinction is made between beliefs regarding the degree to which interoceptive signals are the object of attention and beliefs regarding one's ability to perceive accurately interoceptive signals. This distinction is difficult to test, however, because of the paucity of measures designed to assess self-reported perception of one's own interoceptive accuracy. This article therefore reports on the development of such a measure, the Interoceptive Accuracy Scale (IAS). Use of this measure enables assessment of the proposed distinction between beliefs regarding attention to, and accuracy in perceiving, interoceptive signals. Across six studies, we report on the development of the IAS and, importantly, its relationship with measures of trait self-reported interoceptive attention, objective interoceptive accuracy, confidence in the accuracy of specific interoceptive percepts, and metacognition with respect to interoceptive accuracy. Results support the distinction between individual differences in perceived attention towards interoceptive information and the accuracy of interoceptive perception.